A new Bothriurus (Scorpiones, Bothriuridae) from the Somuncura Plateau, with additions to the knowledge to the endemic scorpion fauna of the area - Ojanguren Affilastro, Andres Alejandro (2010)
Bothriurus nendai n. sp. is described. This species is endemic to the upper level of the Somuncura plateau, a Patagonian island placed in the Monte Phytogeographic province. This is the third known endemic scorpion from this area. Bothriurus nendai n. sp. is closely related to the patagonicus group; however, several morphological characters separate B. nendai from the species of this group. New data on the scorpion species of the plateau are also provided.